Revealing Istidraj as a Hidden Divine Test: Thematic Analysis of Surah Al-An'am 44 in Ibnu Katsir's Tafsir - Putri, Aisyah Cendikia; Nugroho, Kharis (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This study examines the concept of istidraj in the Qur’an, focusing on Surah Al-An’am verse 44 and its interpretation by Ibnu Katsir. The purpose of this research is to clarify the meaning of istidraj the phenomenon where Allah grants ongoing worldly pleasure and prosperity to individuals who persist in disobedience as well as to identify the consequences described in classical tafsir. Employing a qualitative descriptive design and a library research approach, this study analyzed primary Islamic sources and authoritative exegeses, including Tafsir Ibnu Katsir and other leading commentaries. The findings reveal that istidraj is not a sign of divine favor, but rather a gradual form of testing or punishment intended for those who ignore spiritual reminders and remain heedless in their wrongdoing. The study concludes that material success can become a spiritual trial, and that true safety lies in faith, gratitude, and self-awareness. These results contribute to a more nuanced understanding of divine wisdom and ethical conduct in Islamic teachings.